2015
DOI: 10.1073/pnas.1508755112
|View full text |Cite
|
Sign up to set email alerts
|

Disease-proportional proteasomal degradation of missense dystrophins

Abstract: The 427-kDa protein dystrophin is expressed in striated muscle where it physically links the interior of muscle fibers to the extracellular matrix. A range of mutations in the DMD gene encoding dystrophin lead to a severe muscular dystrophy known as Duchenne (DMD) or a typically milder form known as Becker (BMD). Patients with nonsense mutations in dystrophin are specifically targeted by stop codon read-through drugs, whereas out-of-frame deletions and insertions are targeted by exon-skipping therapies. Both t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 61 publications
(63 reference statements)
4
25
0
Order By: Relevance
“…We observed less dystrophin expression in ΔEx7-11 iPSC-derived cardiomyocytes compared with control iPSC-derived cardiomyocytes and the other corrected lines, ΔEx3-9 and ΔEx6-9. Previously, it was shown that missense mutations associated with the DMD phenotype caused steady-state decreases in dystrophin protein levels inversely proportional to the tertiary stability and directly caused by proteasomal degradation (41). Consistent with this report, we observed increased dystrophin protein levels when ΔEx7-11 iPSC-derived cardiomyocytes were treated with the proteasome inhibitor MG-132, as measured by Western blot analysis ( Figure 4F and Supplemental Figure 1C).…”
Section: Resultssupporting
confidence: 90%
“…We observed less dystrophin expression in ΔEx7-11 iPSC-derived cardiomyocytes compared with control iPSC-derived cardiomyocytes and the other corrected lines, ΔEx3-9 and ΔEx6-9. Previously, it was shown that missense mutations associated with the DMD phenotype caused steady-state decreases in dystrophin protein levels inversely proportional to the tertiary stability and directly caused by proteasomal degradation (41). Consistent with this report, we observed increased dystrophin protein levels when ΔEx7-11 iPSC-derived cardiomyocytes were treated with the proteasome inhibitor MG-132, as measured by Western blot analysis ( Figure 4F and Supplemental Figure 1C).…”
Section: Resultssupporting
confidence: 90%
“…Indeed, when many of the same missense mutations were examined in full-length Dys, changes in binding affinity were modest or statistically insignificant (48). This suggests that for DMD and BMD, missense mutations that perturb the core fold of ABD1 CH domains are promoting disease via a misfolding-induced degradation mechanism (49). For some missense mutations-perhaps those that are more superficially located within the ABD1, or those that do not misfold the ABD1 but perturb stability-a functional impact like that discussed above for ABDs in general may become relevant.…”
Section: Discussionmentioning
confidence: 99%
“…As a significant component of the dystrophin-glycoprotein complex (DGC), dystrophin, plays a key role in the contraction of sarcomeres [13]. Dystrophin is a structural protein of 427-kD, consisting of a N-terminal actin binding domain (ABD1), a central rod region, a cysteine-rich (CR) globular domain, and a C-terminal tail (CT) [13]. The C-terminus is associated with glycoproteins and the N-terminus is associated with actin or actin-like proteins [1].…”
Section: Discussionmentioning
confidence: 99%